The Effect of Increased Standardized Ileal Digestible Lysine through Increased Soybean Meal During Late Gestation on Lactating Sow Performance - Abigail K. Jenkins; Jason C. Woodworth; Jordan T. Gebhardt; Robert D. Goodband; Mike D. Tokach; Joel M. DeRouchey (Kansas Agricultural Experiment Station Research Reports, 2024)
A total of 87 sows (Line 241, DNA) and their offspring were used to evaluate the effect of increasing SID Lys through increasing soybean meal concentration in late-gestating sow diets on sow and litter lactation performance. Sows were blocked by parity and body weight (BW) on approximately d 90 of gestation and allotted to one of three treatments of increasing SID Lys (0.60, 0.80, or 1.00%) through increased soybean meal (14, 21, or 29% of the diet). Sows received approximately 4.5 lb/d of their treatment diet for an average SID Lys intake of 11.9, 15.8, or 19.9 g/d, respectively. Diets were fed from d 90 of gestation until farrowing. After farrowing, all sows were fed a common lactation diet containing 1.10% SID Lys. Litters were cross-fostered within sow treatment by 48 h after farrowing to equalize litter size. Parity was included in the statistical model as a fixed effect with sows being classified as either as primiparous (n = 35) or multiparous (n = 52). Weight gain from d 90 to d 110 of gestation increased as SID Lys increased (linear, P < 0.001). Change in urinary creatinine level from d 90 until d 110 of gestation tended to decrease as SID Lys level in the late gestation diet increased (linear, P = 0.063) indicating less muscle catabolism. Piglet ADG from d 2 to d 10 of lactation increased as SID Lys fed in gestation increased (linear, P = 0.017). There was a quadratic effect of late gestation sow diet on litter gain from d 2 until weaning (quadratic, P = 0.044). Litters from sows fed the 0.80% SID Lys diet tended to have numerically greater lactation litter gain. Sows fed the 0.80% SID Lys diet had numerically the highest (quadratic, P = 0.025) piglet mortality during the first two days of lactation. There was a parity × gestation diet interaction for d 2-to-weaning pre-weaning mortality (P = 0.049) where pre-weaning mortality increased as SID Lys increased in primiparous sows but decreased as SID Lys increased in multiparous sows. In conclusion, increasing SID Lys through increased SBM linearly increased late-gestation sow BW gain and piglet ADG during the first portion of lactation. However, litters from sows fed 0.80% SID Lys in late gestation had the highest litter ADG during late lactation and overall. These results suggest that increasing SID Lys intake to 0.80% during late gestation may be beneficial in improving lactation performance.
Keywords: gestating sow; lactating sow; lysine